Resistance and Christian Ethics in Africa - William I. Orbih (Religions)
Colonialism in Africa rewarded individuals who offered no resistance to its ideology and demonized those who did. An effect this continues to have on the African moral imagination is the tendency to idealize compliance over resistance, especially to Western hegemony. Given Africa’s sociopolitical struggles and the consequence of the continent’s ongoing entrapment in the colonial power matrix, I explore ways ethical discourses on the continent can contribute to the ongoing interdisciplinary process of decolonization. In engagement with African literature and decolonial studies on the one hand and liberation ethics on the other, this article proposes a Christian ethics for Africa, discussing resistance as both a moral imperative in postcolonial contexts and a constitutive of the Christian identity.